‘Western Communication’: Eurocentrism and Modernity: Marks of the Predominant Theories in the Field - Erick R. Torrico Villanueva (History of Media Studies)
Cultural imperialism was once the subject of a vibrant debate in international scholarship. Yet, the debate on cultural imperialism has lost much of its previous influence and centrality. This does not mean that cultural imperialism has lost its relevance. On the contrary, in the wake of the neoliberal globalization process, cultural imperialism is now stronger than ever. This article argues that cultural imperialism comprises two dimensions: media imperialism and intellectual imperialism, and it is important to understand how they interact. To illustrate how their interplay works and what consequences follow, the article examines how US academic institutions educated and organized Brazilian media elites who helped to legitimate Lava Jato, a politically driven judicial operation that led to the downgrade of Brazilian democracy, and ultimately paved the way to the rise of Jair Bolsonaro to the presidency. | En un tiempo el imperialismo cultural fue tema de debate acalorado en los estudios internacionales. Sin embargo, dicho debate ha perdido gran parte de su anterior influencia y centralidad, lo que no quiere decir que el imperialismo cultural carezca hoy de relevancia; al contrario, como secuela del proceso neoliberal global se ha fortalecido más que nunca. En este artículo se argumenta que el imperialismo cultural abarca dos dimensiones—el imperialismo mediático y el imperialismo intelectual—y que es importante entender cómo interactúan. Para ilustrar dicha interacción y sus consecuencias, se analiza cómo las instituciones académicas estadounidenses formaron y organizaron a las élites mediáticas brasileñas que ayudaron a legitimar Lava Jato, una operación jurídica con fines políticos que terminó degradando la democracia brasileña y allanando el camino para que Jair Bolsonaro llegara a la presidencia.